PEMBERDAYAAN PENJUAL BUNGA MELALUI EDUKASI DAN PELATIHAN PENGOLAHAN LIMBAH BUNGA MENJADI DUPA - Sharfina Puteri Amima; Muhammad Rahmattullah; Dwi Atmono (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
The city of Banjarmasin, South Kalimantan, is known for its strong pilgrimage culture, attracting thousands of daily visitors to three main locations: Makam Guru Zuhdi, Kubah Habib Basirih, and Makam Sultan Suriansyah. This high volume of visitors generates a significant amount of pilgrimage flower waste, most of which ends up in the landfill. According to data from the South Kalimantan Environmental Agency in 2023, organic waste contributes 55.89% of Banjarmasin's total daily waste, with plant waste, including flowers, accounting for 4.2%. Flower waste at these pilgrimage sites ranges from 3 to 5 kilograms per day, increasing to 10-20 kilograms during the haul season. Despite its economic and ecological potential, the utilization of this waste has not been optimal. Previous studies by Waghmode & Gunjal (2018) and Ratna M. (2023) show that floral waste can be processed into value-added products and help reduce pollution. This community service activity aims to empower flower vendors by transforming floral waste into environmentally friendly and economically valuable incense products. Through the "Mandupa" community service program, we provide innovative education and training to 30 flower vendors in Banjarmasin. The methods used include socialization, practical training in making natural incense, and marketing assistance. The results of the activity show that the participants were able to independently master the techniques of processing floral waste into incense. This program not only succeeded in increasing environmental awareness but also opened new economic opportunities for flower vendors. Positive feedback confirms the program's success in improving skills and economic well-being.